What Factors Are Predictive of Outcome in the Treatment of Soft Tissue Sarcomas of the Foot and Ankle?. Issue 1 (February 2017) - Houdek, Matthew T.; Beahrs, Taylor R.; Wyles, Cody C.; Rose, Peter S.; Sim, Franklin H.; Turner, Norman S.
Soft tissue sarcomas of the foot and ankle are common. Currently, there exist limited data on prognostic variables. The aim of this study was to review our institution's experience with soft tissue sarcomas of the foot and ankle to identify factors affecting outcomes and survivorship. We reviewed the records of 62 foot and ankle soft tissue sarcomas treated with definitive surgery at our institution between 1992 and 2013. The cohort consisted of 35 males and 27 females with a mean age at diagnosis of 45 years and a mean follow-up of 7 years. The most common tumor subtype was synovial sarcoma (n = 16). The overall limb salvage rate was 53%. Local recurrence was observed in 9 patients and distant metastases in 15 patients. Tumor size ≥3 cm in maximal dimension was the greatest risk factor in mortality. Posttreatment complications occurred in 15 patients. Local recurrence and development of distant disease was relatively common following wide excision of a soft tissue sarcoma of the foot and ankle. Tumors that were ≥3 cm in maximal dimension were associated with a worse overall survival and patients with neoadjuvant radiation were at increased risk of complications. Levels of Evidence: Level IV: Retrospective Case Series